METODE PEMBELAJARAN DALAM KEPERAWATAN JIWA: LITERATURE REVIEW - Cindy Claudia Ginting; Sri Wahyuni; Darwin Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Mental nursing is the application of knowledge about human behavior, psychosocial, and personality theories. One that applies mental nursing is nursing students with several learning methods. The purpose of this study is what are the effective learning methods in mental nursing. this study used a literature review design. Whit articles 2016-2020 via Google Scholar, Smantic Scholar, and Portal Garuda. Results: The results of the literature review consist of methods, namely Blanded Learning, Student Teams Achievement Divisions (STAD), Focus Group Discussion (FGD), and Role Playing. From these 4 articles, there are variatios in learning methods using role play, group discussions and videos. The role play method can improve communication skills and abilities. While the STAD method can improve student achievement competence. Most of the articles reviewed used the role play method of learning in its implementation. So that all learning methods in the articles that have been reviewed can improve student abilities effectively. Keywords: Learning methods, mental nursing, students